Pengembangan Komik Digital Berbasis CTL Untuk Pemahaman Konsep IPA dan Motivasi Belajar Siswa Sekolah Dasar - Ade Rahayu; Agung Tri Prasetyo; Cahyo Budi Utomo (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study is prompted by various discoveries, including the fact that teachers have not used learning media efficiently, resulting in students who do not comprehend the notion of learning and a lack of student interest in the learning process. The goal of this study was to create Contextual Teaching and Learning (CTL) based digital comic media and assess its practicality, efficacy, and students' reactions to it to improve students' conceptual comprehension and motivation in scientific learning. This is a sort of development study. The development model employed is a 4-D model that includes steps for defining, designing, creating, and deploying. The results revealed that digital comic validation was performed based on numerous factors, with the material aspect receiving an average of 3.6 with the Very Valid criterion. Using the Extremely Valid criterion, the aspects of the questions received an average of 3.6. Using the Valid criterion, Display Aspect received an average of 3.46. The final test results following the media application revealed that the average student learning outcomes in the experimental class were greater than those in the control class. The analysis of the findings of students filling out the motivation to learn questionnaire is likewise at a very high level.